THE ROLE OF SCHOOL PRINCIPALS’ LEADERSHIP IN IMPROVING EARLY CHILDHOOD EDUCATION (ECE) TEACHER COMPETENCE - Sinta; Asma Kurniati; Siti Misra Susanti; Ratna Said (Universitas Muhammadiyah Makassar, 2026)
The urgency of this study arises from the suboptimal competence of early childhood education (ECE) teachers, which is influenced by variations in school principals’ leadership quality, and from the lack of a comprehensive synthesis of previous research findings on the relationship between these two variables. This study aims to analyze the role of school principals’ leadership in improving ECE teachers' competence and to identify effective leadership strategies informed by prior research. The method employed is a Systematic Literature Review (SLR) with a descriptive approach, utilizing data sources in the form of scientific articles indexed in SINTA 1, 2 and 3 obtained through Google Scholar, and analyzed using content analysis techniques guided by the PRISMA framework. The results indicate that school principals’ leadership plays a significant role as an academic supervisor, motivator, and facilitator in enhancing teacher competence and implementing strategies such as academic supervision, teacher empowerment, and the creation of a collaborative work environment. These findings suggest that the effectiveness of school leadership directly contributes to improving the quality of early childhood education learning. The novelty of this study lies in the systematic integration of empirical findings through an SLR, providing a comprehensive overview of the roles and strategies of school leadership. This study contributes theoretically to the development of educational leadership studies and, in practice, as a basis for formulating policies and strategies to improve ECE teacher competence.